Analisis Interaksi Obat Hiperlipidemia pada Pasien PT. Pertamina di Salah Satu Apotek Kimia Farma di Bandung - Widi Astuti; Meiti Rosmiati (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Hyperlipidemia is an abnormal condition of lipid metabolism which is characterized by an increase in lipid levels in the blood. Hyperlipidemia is often accompanied by other diseases. So the treatment of hyperlipidemia is often combined with other drugs and has the potential to increase the occurrence of drug interactions. Drug interaction is a condition in which a substance or drug activity can produce an increased or decreased effect or produce a new effect. This study aims to determine the presence of hyperlipidemic drug interactions in patients with diabetes mellitus Pertamina in one of the chemical pharmacies in Bandung based on the number of patients, number of cases, interaction mechanism and severity. This study uses a non-experimental research method with a descriptive approach and data collection is taken retrospectively based on prescription sheet data for the March 2021 period. The number of samples taken is 87 prescription sheets that meet the inclusion criteria. Data were analyzed descriptively usingliterature Stockley's Drug Interaction Handbook. Of the hyperlipidemic patients, who had the potential to experience drug interactions as many as 28 Prescriptions. Based on the results of the study, it was found that the severity of drug interaction cases which stated the severity level of major interactions was 1%, Moderate was 30% and minor was 1% while those that did not interact were 68%. Based on the results of the study above, the researchers concluded that there were 28 cases of prescription sheets containing hyperlipidemia drug interactions in March 2021 at Kimia Farma Pharmacy. The level of drug interactions consisted of major, moderate and minor categories with a severity level of 1% for the major category, 30% for the moderate category, 1% for the minor category, while 68% had no interactions.